Patient Compliance with Taking Oral Antihypertensive by Methods Pill-Count and MMAS-8 at the Clinic - Ferika Indrasari; Mutiara Desy Fitria; Sri Suwarni; Nanda Dwi Akbar (GLOBAL HEALTH SCIENCE GROUP, 2026)
In Indonesia, hypertension occupies the fourth highest position as a deadly disease. The prevalence of hypertension in Central Java reached 37.57% based on measurements for the ≥18 year old population. Hypertension uncontrolled if not treated immediately can cause complications disease. Complications can be prevented by dutifully taking medication. Adherence to taking medication was what really determines the success of treatment therapy. Compliance Drink medicament can measured with using method Pill-Count and self report. Method Pill-Count was carried-out by calculating the patient's remaining medication. Meanwhile self report thiswas carried-out by giving an MMAS-8 questionnaire that consist of 8 written list of questions to the patient. This study aims to determine the level of patient adherence to drug use oral antihypertensives by method pill- count in hypertensive patients in the Clinic and correlation between methods Pill-Count and MMAS-8. This research is a type of non-experimental research with observational methods that are quantitatively correlative with design data collection prospective. Sampling techniques using techniques total sampling. The number of samples used was 31 samples. Source data taken from the questionnaire sheet and analysis used in this research is analysis univariate, analysis bivariate, test chi-square and correlation test spearman rank. Validity was assessed using Pearson correlation with r-table = 0.279, and reliability was evaluated using Cronbach’s alpha. The results of the study obtained that the patient's level of compliance from the test chi- square has a sig value of 0.008<0.05 which means the patient's level of compliance with using oral antihypertensive drugs using the method pill-count and MMAS-8 in the clinic is classified as compliant. Test spearman rank shows that there is a relationship between the level of adherence to taking antihypertensive drugs and the method Pill-Count and MMAS-8 which has a sig value result of 0.008 < 0.05. The results of this study show that patient compliance on usage medicament oral antihypertensives in clinic classified as a medium level of relationship.